Liquefaction Behaviors of Oil Palm Frond and Bamboo in 1-Butyl-3-Methylimidazolium Chloride - Zhong Sheng Tai; Mohd Asmadi; Noorhalieza Ali (Bulletin of Chemical Reaction Engineering & Catalysis, 2018)
Oil palm and bamboo are two of the most widely used biomass in the world nowadays as they can be converted into many valuable products. However, they are very difficult to be hydrolyzed and converted into other products because of their tight and strong hydrogen bonding between the lignin and polysaccharides. Ionic liquid (IL) is said to be the most ideal solvent to dissolve those biomass. Thus, in this research, 1-butyl-3-methylimidazolium chloride ([BMIM][Cl]) was chosen to liquefy oil palm frond (OPF) and bamboo. The objective of this research was to compare the reaction behaviors of OPF and bamboo in [BMIM][Cl] at different treatment time. OPF and bamboo were heated at 120 °C for 2-24 hours under atmospheric pressure. Two fractions were obtained, namely [BMIM][Cl]-soluble and -nonsoluble. The non-soluble fractions were characterized using TGA, FTIR, XRD and FESEM while the soluble fractions were analyzed using HPLC. Based on the results obtained from the analyses, the effectiveness of [BMIM][Cl] in dissolving OPF was higher than bamboo as it was made up of less complex and compact cell wall structure. This structure allowed the diffusion of [BMIM][Cl] into the interior of OPF more easily to break down the hydrogen bonding network. Holocelluloses and lignin of OPF solubilized into [BMIM][Cl] more rapidly due to the greater distortion in hydrogen bonding network of the cell wall with the increase in treatment time compared to bamboo. Moreover, the mono-sugars of OPF were formed much easily than bamboo after short period (2 hours) of treatment.